2012
DOI: 10.1161/circulationaha.112.118778
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 5–Mediated Hyperphosphorylation of Sirtuin-1 Contributes to the Development of Endothelial Senescence and Atherosclerosis

Abstract: Background-Endothelial senescence represents one of the major characteristics of vascular aging and promotes the development of atherosclerosis. Sirtuin-1 (SIRT1) is an NAD-dependent deacetylase possessing antiaging activities. During the occurrence of endothelial senescence, both the expression and activity of SIRT1 are downregulated. The present study was designed to investigate the molecular mechanisms contributing to the loss-of-SIRT1 function in senescent endothelial cells. Methods and Results-After repet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 52 publications
(62 reference statements)
2
85
0
Order By: Relevance
“…14,36 Previous findings indicated that Rap1 directly binds to the IKK complex in Hela S3 carcinoma cells, 10 but directly associates with IkBa in primary culture of porcine aortic endothelial cells (PAECs). 37 The present results on macrophages are in line with the former observation that Rap1 binds directly to the IKK complex. Indeed, the present co-immunoprecipitation experiments revealed that Rap1 binds directly to both IKKa and IKKb, but not to IkBa.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…14,36 Previous findings indicated that Rap1 directly binds to the IKK complex in Hela S3 carcinoma cells, 10 but directly associates with IkBa in primary culture of porcine aortic endothelial cells (PAECs). 37 The present results on macrophages are in line with the former observation that Rap1 binds directly to the IKK complex. Indeed, the present co-immunoprecipitation experiments revealed that Rap1 binds directly to both IKKa and IKKb, but not to IkBa.…”
Section: Discussionsupporting
confidence: 92%
“…[42][43][44] Indeed, in senescent PAECs, the amount of Rap1 in the cytosol is elevated compared with young PAECs. 37 Thus, it is tempting to speculate that as telomere length is reduced, the ratio between telomere-bound and "free" Rap1 (available for the cytoplasmic activation of the NFkB pathway) is affected. This hypothesis implies that Rap1 could be an important molecular switch that links aging to chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In ECs, increased cyclin-dependent kinase 5-mediated hyperphosphorylation of SIRT1 at Ser-47 prevents its nuclear exportation and the interaction with telomeric repeat-binding factor 2-interacting protein 1 (TERF2IP), a regulator of telomere function and NF-jB signaling (12).…”
Section: Sirt1 In Cell Senescence and Aging Processesmentioning
confidence: 99%
“…Abstract: Background-P25 is a 209-amino acid COOH-terminal fragment of the regulatory subunit 1 (p35) for CDK5, a proline-directed serine/threonine kinase. Upregulation of p25 triggers a sustained activation of CDK5 and hyperphosphorylation of various substrates including SIRT1, the longevity regulator, in endothelial cells (1). The present study investigated the role of endothelial p25 in regulating endothelial senescence and adverse arterial remodeling.…”
Section: Board:mentioning
confidence: 93%